Factors associated with the implementation of dialectical behavior therapy by Spanish speaking mental health professionals who treat suicide risk - María V. Navarro-Haro; Alba Abanades; Óscar Peris-Baquero; Pablo Gagliesi; Demián Rodante; Azucena García-Palacios; Jorge Osma (BMC Psychiatry, 2024)
Abstract Background The lack of training for professionals on how to manage suicide risk is an important barrier to effective intervention. Dialectical Behavior Therapy Intensive Training™ (DBT-IT) includes specific training for suicide and has shown promising results to enhance implementation of DBT. To our knowledge, no published studies have evaluated the effect of DBT-IT on therapists’ attitudes towards treating suicide risk and among Spanish-speaking mental health professionals. The main aim of this study was to evaluate the effect of DBT-IT on therapists’ attitudes regarding treating suicide risk and its relationship with the implementation of DBT before and after receiving DBT-IT. Methods A total of 242 mental health workers (76.4% women, mean age 35.38, SD = 9.17; 77.7% from Latin America; 22.3% from Spain) who had received a DBT-IT participated in the study. Self-efficacy (Efficacy in Assessing and Managing Suicide Risk Scale) and concerns (Concerns about Treating Suicidal Clients Scale) in treating suicide, perceived burnout (Copenhagen Burnout Inventory), confidence in applying DBT (Behavioral Anticipation and Confidence Questionnaire), barriers to implementation (Barriers to Implementation Inventory), implementation of DBT and reach were measured via online survey at parts 1 (pre-training) and 2 (post-training, after 9 months of implementation) of the DBT-IT. Results Differences between pre-training and post-training (n = 61) indicated statistically significant improvements in self-efficacy, concerns about the lack of training and competence in treating suicide, and confidence in applying DBT. Statistically significant increases in the rates of DBT treatment modes implementation (except for individual therapy) and mindfulness practice, as well as the number of team members and consultation team hours, were also found. Findings also indicated statistically significant positive correlations between burnout and concerns about treating suicidal clients, as well as with structural and administrative implementation barriers, and between self-efficacy in managing suicide, confidence in applying DBT and implementation of DBT treatment modes. Participants with more implementation barriers reported lower rates of consultation team meetings and phone coaching implementation. Conclusions DBT-IT could be an adequate training model to increase self-efficacy and confidence in treating suicide risk as well as to facilitate implementation of DBT treatment modes by Spanish-speaking mental health professionals. Clinical trial number Not applicable.